2022
DOI: 10.1007/s10570-022-04792-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose-based membrane as a potential material for high performance biodegradable aerosol respirators for SARS-CoV-2 prevention: a review

Abstract: The controversy surrounding the transmission of COVID-19 in 2020 has revealed the need to better understand the airborne transmission route of respiratory viruses to establish appropriate strategies to limit their transmission. The effectiveness in protecting against COVID-19 has led to a high demand for face masks. This includes the single-use of non-degradable masks and Filtering Facepiece Respirators by a large proportion of the public, leading to environmental concerns related to waste management. Thus, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…for WPF-3 to 52.57% for WPF-3/CNF-60 and the density increased from 0.32 to 0.73 g/cm 3 , which indicated that the structure of WPF-3/CNF-60 was much denser. The optical images shown in Figure S4 also indicated that the transparency of the hybrid cellulose fibrous membranes increased with the increment of the dosage of CNFs, indicating the decrease in porosity.…”
Section: Properties Of the Hybrid Fibrous Membranementioning
confidence: 93%
See 2 more Smart Citations
“…for WPF-3 to 52.57% for WPF-3/CNF-60 and the density increased from 0.32 to 0.73 g/cm 3 , which indicated that the structure of WPF-3/CNF-60 was much denser. The optical images shown in Figure S4 also indicated that the transparency of the hybrid cellulose fibrous membranes increased with the increment of the dosage of CNFs, indicating the decrease in porosity.…”
Section: Properties Of the Hybrid Fibrous Membranementioning
confidence: 93%
“…Where 1.54 (g/cm 3 ) is the density of the pure fibrous membrane and d (g/cm 3 ) is the density of the sample. 37 3 | RESULTS AND DISCUSSION…”
Section: Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, owing to the optimized graphitic structure and the sufficient interaction between rigid OLC and fiber matrix, the strength and toughness of CNFs are simultaneously enhanced. Improving the mechanical properties of the nanofibers can reduce the problem of fiber breaking during the deformation process in their actual use and thus avoid the degradation of their application performance, thus the OLC-reinforced CNFs can be further developed as electrode material in wearable devices as well as absorption and filtration material in masks, filters, and other devices, etc. Furthermore, this research can also provide some theoretical support for the industrial production of next-generation high-strength, high-modulus, and high-toughness carbon fibers.…”
Section: Introductionmentioning
confidence: 93%
“…Hydrogels are solid-liquid systems with three-dimensional cross-linked networks, formed by a variety of watersoluble polymers. It is possible to formulate gels with of microbeads (Coombs OBrien et al 2017), for preparing air-filtering systems (Lippi et al 2022;Stanislas et al 2022), and as a component in composite materials (Miao and Hamad 2013;Riva et al 2021;Lan et al 2022;Tanpichai et al 2022).…”
mentioning
confidence: 99%